Missing teeth and its impact on oral function of the patients visiting dental colleges in kathmandu - Rijal, Arjun Hari; Pokharel, Prenit; Lama, Tshiring; Pandey, Nashib; Shrestha, Bidhan; Shrestha, Ashwin (Birat Journal of Health Sciences, 2024)
Introduction: In the present scenario oral diseases are more prevalent in the large population. Missing teeth is one of them which have negative impact on oral health related quality of life. Objectives: The aim of this study was to investigate how tooth loss affects the oral health related quality of life through an Oral Health Impact Profile-14 (OHIP-14) questionnaire and additional questions among patients visiting the six different Dental Colleges in Kathmandu, Nepal. Methodology: The descriptive cross-sectional study was conducted from Asar to Manshir 2078. Patients visiting the prosthodontics outpatient department (OPD) during the study period were enrolled until the desired sample size was met. Co-investigators assigned in every dental colleges were responsible for the data collection. Data was obtained from a questionnaire based on the OHIP-14 form, additional questions and a clinical examination. Assistant Research officer was responsible for coordination among the researchers. Data from completed forms were entered into Microsoft excel and analyzed with SPSS v21 to investigate how tooth loss affects the oral health related quality of life (OHRQoL). Results: Mean age of the participants was 47.6 years. Out of 380 participants 119 (48 %) were males and rest were females. The mean number of missing teeth was 5, and the mean total OHIP-14 score was 21.57±12.55. The most frequently impacted dimensions for the OHIP-14 were “Physical pain” (77 %) and “Psychological discomfort” (82.5 %). 367 (96.8 %) of the investigated population experienced some form of impact due to missing teeth on their OHRQoL. Conclusion: A large majority of the patients visiting different Dental Colleges experienced an impact on their OHRQoL due to the missing teeth. The number of missing teeth had an impact on OHRQoL, but the position of missing teeth had not. The OHIP score with the criteria used in this study was found to be higher in comparison to other international findings.